Security Issues in Internet of Things: A Comprehensive Review - Khan Sial, Muhammad Fateh (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
IoT devices can be insecure and may not be able to defend themselves against a wide variety of security threats. This is primarily due to the reason that resources on IoT devices are limited. Standards that govern the development of these devices are not yet mature. Moreover, the design, development and deployment of the software and hardware is not at all secure. The solution to these problems is that a global mechanism should be developed that is robust for securing the IoT layers. Major bottleneck in this approach is that the resources in IoT devices are very diverse in nature, based on several technologies and protocols which make it quite challenging to develop a universal protocol to meet the security threats. These threats have been divided into low level, middle level and high level layers of IoT. In this article, various mechanisms for handling security issues at different IoT layers have been reviewed. Attacks in IoT, their implications, solutions and role of Blockchain technology to address these problems are briefly presented.